Palestina dalam Pusaran Sejarah dan Solidaritas Umat Islam: Palestine in the Vortex of History and Muslim Solidarity - Azwar, Azwar; Abd. Rahim Yunus; Susmihara, Susmihara (DIRASAH: Jurnal Kajian Islam, 2025)
The Israel-Palestine conflict is one of the most complex and prolonged issues in modern history, particularly within the context of the Islamic world. This study aims to examine the historical roots of the establishment of the state of Israel and the loss of Palestinian sovereignty, explain the main dynamics of the conflict from the 20th century to the present, analyze the response of the Islamic world, and evaluate the various efforts made toward conflict resolution. Using a descriptive-qualitative method and a historical approach, this research relies on literature review from academic works, official documents, and other credible sources. The findings show that the conflict is rooted in colonialism, the Zionist project, and Western policies following the fall of the Ottoman Caliphate. The declaration of the establishment of Israel in 1948 marked the beginning of open conflict and a humanitarian tragedy for the Palestinian people. The Islamic world generally demonstrates moral and religious solidarity with Palestine, though concrete actions among Islamic countries often lack unity. Peace efforts made over the past decades have frequently faced obstacles due to political interests and power imbalances. Therefore, a comprehensive understanding of this conflict requires a historical, political, and humanistic approach in order to promote a just and sustainable resolution for all parties involved.